Postoperative Evaluation of Moyamoya Disease with Perfusion-Weighted MR Imaging: Initial Experience - Lee, Seung-Koo; Kim, Dong Ik; Jeong, Eun-Kee; Kim, Si-Yeon; Kim, Sang Heum; In, Yon Kwon; Kim, Dong-Seok; Choi, Joong-Uhn (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Encephaloduroarteriosynangiosis (EDAS) has become the main treatment for moyamoya disease, a chronically progressive cerebrovascular occlusive disease in children. We aimed to assess the utility of perfusion-weighted MR imaging for evaluating hemodynamic changes before and after EDAS.METHODS: Thirteen patients with angiographically confirmed moyamoya disease who underwent EDAS were investigated, and results were compared with those of a control group (n = 5). Perfusion MR imaging was performed before and after EDAS by using a T2*-weighted contrast material-enhanced technique. Relative cerebral blood volume (rCBV) and time to peak enhancement (TTP) maps were calculated. Relative ratios of rCBV and TTP in the middle cerebral artery (MCA) and basal ganglia were measured and compared with those of the posterior cerebral artery (PCA). Changes in hemodynamic parameters between pre- and post-EDAS perfusion maps were investigated.RESULTS: The mean rCBV ratio of MCA to PCA in the patient group was slightly higher than that in the control group, without statistical significance. All 13 patients showed a delayed TTP in the MCA before EDAS compared with the control group (P = .0006), and the TTP after EDAS was significantly reduced (P = .0002). In the basal ganglia, shortening of the TTP was demonstrated before EDAS, but no significant change was observed after EDAS.CONCLUSION: Perfusion-weighted MR imaging can be applied for evaluating postoperative changes in cerebral blood flow in moyamoya disease. Shortening of the TTP in the MCA of the hemisphere operated on is a marker for the development of collateral circulation from the external carotid artery to the internal carotid artery.